Policy research in accounting: A doctrinal research perspective - Daniël Coetsee (Journal of Economic and Financial Sciences, 2019)
Orientation: The accounting literature acknowledged that a gap exists between accounting research and accounting practice and supported the argument that accounting research does not significantly contribute to accounting practice.